WhatsApp Management for Effective Online Learning in Fiqh Subjects and ITS Implications for Character Education - Tatang Ibrahim (AL-ISHLAH: Jurnal Pendidikan, 2022)
The effectiveness of using Whatsapp media as an online learning medium has yet to be tested. Especially if it is associated with character education which is the essence of education itself. This study aims to 1) to find out how the teacher's activities in online-based learning using WhatsApp media at Madrasah Ibtidaiyah, 2) to find out how the learning outcomes of Madrasah Ibtidaiyah students are using WhatsApp media, 3) to find out how the parents of Madrasah Ibtidaiyah students respond to the use of WhatsApp as an online-based learning media. The research method used is descriptive quantitative, which produces findings that 1) teacher activity in online-based learning using WhatsApp media is still low with a percentage of 69.30% being in the sufficient category. 2) student learning outcomes using WhatsApp as an online learning medium have not been achieved classically with a percentage of 76.9%. 3) parents' responses to WhatsApp as an online learning medium are positive with a percentage of 82%. The use of WhatsApp as a learning medium at the Madrasah Ibtidaiyah level is less effective, so the implication is that it does not support the implementation of Character Education at Madrasah Ibtidaiyah.